Ex-situ additively manufactured FeCrMoCB/Cu bulk metallic glass composite with well wear resistance. (October 2021) - Zou, Yongming; Qiu, Zhaoguo; Zheng, Zhigang; Wang, Gang; Yan, Xingchen; Yin, Shuo; Liu, Min; Zeng, Dechang
Abstract: Tribological properties and wear mechanisms of ex-situ additively manufactured FeCrMoCB/Cu bulk metallic glass composite (BMGC) under different normal loads and sliding speeds were investigated. The unique amorphous/crystalline microstructure provided FeCrMoCB/Cu BMGC with well wear resistance including low wear rate and coefficient of friction (COF). Both the wear rate and COF showed the same tendency as the variation of normal load. However, the COF decreased but the wear rate increased with the increasing sliding speed. Moreover, the wear mechanisms changed from abrasive wear to oxidation wear and adhesive wear when increasing the normal load, while the adhesive wear and fatigue wear became dominated as the sliding speed increased. Highlights: Ex-situ FeCrMoCB/Cu BMGC with low wear rate and friction coefficient was fabricated. Amorphous/Crystalline composite microstructure improve the tribological properties. Wear mechanisms changed with the normal load and sliding speed.